2013
DOI: 10.1177/0956797613486982
|View full text |Cite
|
Sign up to set email alerts
|

Literacy and Numeracy Are More Heritable Than Intelligence in Primary School

Abstract: Because literacy and numeracy are the focus of teaching in schools, whereas general cognitive ability (g, intelligence) is not, it would be reasonable to expect that literacy and numeracy are less heritable than g. Here, we directly compare heritabilities of multiple measures of literacy, numeracy, and g in a United Kingdom sample of 7,500 pairs of twins assessed longitudinally at ages 7, 9, and 12. We show that differences between children are significantly and substantially more heritable for literacy and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
61
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 33 publications
1
61
1
2
Order By: Relevance
“…However, genetic research has shown that individual differences in educational achievement are substantially heritable (9)(10)(11). Indeed, we have shown that educational achievement is significantly more heritable than intelligence in the early school years (12). We have recently found high heritability (58%) for the results of a nationwide examination, the General Certificate of Secondary Education (GCSE), which is administered in the United Kingdom at the end of compulsory education at age 16 (13).…”
mentioning
confidence: 99%
“…However, genetic research has shown that individual differences in educational achievement are substantially heritable (9)(10)(11). Indeed, we have shown that educational achievement is significantly more heritable than intelligence in the early school years (12). We have recently found high heritability (58%) for the results of a nationwide examination, the General Certificate of Secondary Education (GCSE), which is administered in the United Kingdom at the end of compulsory education at age 16 (13).…”
mentioning
confidence: 99%
“…Quantitative genetic studies, using twin, adoption and other family designs, have found all complex human traits to be heritable to some degree. For example, school achievement is substantially heritable, with genetic differences accounting for approximately 60% of the variation among primary school students (e.g., Kovas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic literacy also includes understanding that for all complex traits, genetic variability within a population is so vast that two randomly selected individuals within a population can be more genetically different from each other than two randomly selected individuals from two diverse populations (Jorde & Wooding, 2004;Witherspoon et al, 2007). Moreover, any differences within and between populations can be due to environmental and/or genetic differences.…”
Section: Introductionmentioning
confidence: 99%
“…Kovas et al, 2005) than substantial heritability of literacy found throughout formal school education (e.g. Harlaar et al, 2005;Byrne et al, 2006;Kovas et al, 2013).…”
mentioning
confidence: 99%
“…Haworth et al, 2010;Polderman et al, 2015;Tucker-Drob & Bates, 2016) also supports the Gene-Gini interplay. Unlike numeracy and literacy, for which heritability remains stably high throughout the school system, heritability of IQ is moderate in primary school and continues to increase throughout education (Kovas et al, 2013). This may be because there is no formal instruction for intelligence, with more variance explained by environmental disparity.…”
mentioning
confidence: 99%